059 Switching CGRP monoclonal antibodies for chronic migraine: real-world outcomes of 37 episodes. Issue 6 (27th May 2022) - Weatherall, Mark; Matharu, Manjit
Abstract : CGRP monoclonal antibodies (mAbs) have been shown in clinical trials to be effective therapies for episodic and chronic migraine. Three CGRP mAbs are licensed for use in the UK: erenumab, freman- ezumab, and galcanezumab. The overall efficacy of these three drugs is similar in published trials, but no head-to-head comparisons have been undertaken. Very little real world data on this question has been published. It is unknown, therefore, whether some patients may respond better to one member of this novel class of migraine therapeutics than others. The authors conducted a retrospective review of patients prescribed CGRP mAbs between 2018–2020, identifying 37 occasions on which a patient was switched from one CGRP mAb to another. In 24 cases, the switch was made because of lack of efficacy; in 13 cases, the switch was made because of side effects, cost, or other logistical factors. Where the switch was made because of lack of efficacy, 11/24 patients found the second CGRP mAb effective in significantly reducing the frequency of migraine days; in all but two of these cases patients moved from chronic migraine to episodic migraine. Where a switch was made for reasons other than efficacy, all patients found both CGRP mAbs were effective. In conclusion, patients with chronic migraine who fail to respond to, or do not tolerate, a first CGRP mAb should be offered treatment with another member of the class. mark.weatherall1@nhs.net